2018
DOI: 10.4049/jimmunol.1800515
|View full text |Cite
|
Sign up to set email alerts
|

IL-36 and IL-1/IL-17 Drive Immunity to Oral Candidiasis via Parallel Mechanisms

Abstract: Protection against microbial infection by the induction of inflammation is a key function of the IL-1 superfamily, including both classical IL-1 and the new IL-36 cytokine families. is a frequent human fungal pathogen causing mucosal infections. Although the initiators and effectors important in protective host responses to are well described, the key players in driving these responses remain poorly defined. Recent work has identified a central role played by IL-1 in inducing innate Type-17 immune responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 51 publications
4
75
0
3
Order By: Relevance
“…Our results fit in a growing list of examples of additional roles for IL-23. A recent report suggested an IL-17-independent IL-23-dependent protective pathway in the context of experimental oropharyngeal candidiasis, which was linked to IL-36 [52]. Two other pivotal studies showed that IL-23 instructs IL-22 production, which in turn promotes dermal inflammation and acanthosis [19] and that IL-23 can drive GM-CSF production, which is essential for the induction of EAE [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Our results fit in a growing list of examples of additional roles for IL-23. A recent report suggested an IL-17-independent IL-23-dependent protective pathway in the context of experimental oropharyngeal candidiasis, which was linked to IL-36 [52]. Two other pivotal studies showed that IL-23 instructs IL-22 production, which in turn promotes dermal inflammation and acanthosis [19] and that IL-23 can drive GM-CSF production, which is essential for the induction of EAE [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, OPC susceptibility in mice does not perfectly phenocopy the human condition. Unlike nearly all humans (5, 86), laboratory mice do not harbor C. albicans as a commensal organism, and hence the acute OPC model system mainly reflects events in the innate response (59, 76, 78, 87). Mice lacking STAT3 in T cells are not susceptible to OPC (76).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of these mechanisms in the epithelial immune responses to C. albicans is yet to be elucidated. et al, 2018), there is evidence available to suggest that IL-23 has IL-17-independent effects (Lee et al, 2015;Maxwell et al, 2015;Verma et al, 2018). These observations highlight the role of IL-36-mediated protection as an independent pathway contributing to immune mucosal protection to C. albicans infections .…”
Section: Role Of Il-36 Cytokines In Anti-candida Responsesmentioning
confidence: 96%
“…While commensal yeasts or low hyphal burdens promote an activation of PI3K/Akt and NF-κB, with weaker, transient activation of p38, JNK, and ERK1/2 MAPK signaling pathways, detection of high levels of C. albicans hyphae results in the strong, sustained activation of all three MAPK pathways. This latter leads to activation of c-Fos within the AP-1 transcription factor and eventually, to the secretion of an array of antimicrobial peptides, alarmins, and pro-inflammatory cytokines (Moyes et al, 2010(Moyes et al, , 2014Verma et al, 2017bVerma et al, , 2018Nikou et al, 2019).…”
Section: Anti-candida Innate Immunity At the Mucosamentioning
confidence: 99%